Preparedness Plan Ensures Dental Service Sustainability During a Public Health State of Emergency - Huong Le; Mary E. Foley (Taylor & Francis Group, 2023)
ABSTRACTBackground In early 2020, the COVID-19 pandemic emerged bringing risk of disease, disability and death to all Americans. As public health officials scrambled to respond, dental offices were shuttered leaving little access to dental care.Methods Collaborating with medical colleagues and partnering with the local public health department, the Asian Health Services (AHS) dental team developed a preparedness plan to ensure the safe and effective ongoing delivery of oral health care services, respond to the national public health state of emergency and support local public health efforts to contain the pandemic.Results AHS dental services remained operational throughout the COVID-19 pandemic due to the swift and strategic response of the dental team. COVID-19 contact tracing, testing and vaccination became new services rendered by dental personnel, which are now integrated into policies, programs and services. Professional education and training were also updated to ensure sustained preparedness.Conclusions By having a comprehensive and coordinated preparedness plan in place, AHS was able to effectively support public health efforts and serve the oral health care needs of the community.Practical Implications Preparedness efforts implemented by a coordinated effort between AHS's medical and dental leadership in cooperation with local public health officials during the recent COVID-19 pandemic may serve as a future model for all health care professionals.